Efektivitas Return Board Terhadap Kemampuan Pukulan Forehand Drive Tenis Meja - Agus Kurniadi; La Robi; Abu Bakar (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This study aims to test the effectiveness of the use of return board in improving the ability to hit forehand drive in Physical Education students of the University of Muhammadiyah Sorong. The approach used is an experiment with a one-group pretest-posttest design. The research sample involved 40 students who were selected based on certain criteria. Measurement of forehand drive ability was carried out before (pretest) and after (posttest) treatment in the form of training using a return board. Descriptive analysis showed that the average forehand drive ability increased from 20.40 (SD = 4.235) in the pretest to 25.85 (SD = 3.438) in the posttest. The results of the normality test confirmed that the data were normally distributed (p > 0.05), and the paired t test showed a significant difference with a mean difference of -5.450 (t = 8.034, p < 0.000). The 95% confidence interval ranged from -6,822 to -4,078, indicating the consistency of improvement in participants' abilities after treatment. A moderate positive correlation between pretest and posttest results (r = 0.390, p < 0.05) indicates the effect of exercise on the improvement of technical skills. The results of this study show that the use of return board is effective in improving forehand drive hitting ability.